CYP2A6 is associated with obesity: studies in human samples and a high fat diet mouse model - Wang, Kesheng; Chen, Xue; Ward, Stephen C.; Liu, Ying; Ouedraogo, Youssoufou; Xu, Chun; Cederbaum, Arthur I.; Lu, Yongke (International Journal of Obesity, 2019)
Background/objectives CYP2A6 (CYP2A5 in mice) is mainly expressed in the liver. Hepatic CYP2A6 expression is increased in patients with non-alcoholic fatty liver disease (NAFLD). In mice, hepatic CYP2A5 is induced by high fat diet (HFD) feeding. Hepatic CYP2A5 is also increased in monosodium glutamate-induced obese mice. NAFLD is associated with obesity. In this study, we examined whether obesity is related to CYP2A6. Subjects/methods Obesity genetic association study: The SAGE is a comprehensive genome-wide association study (GWAS) with case subjects having a lifetime history of alcohol dependence and control subjects never addicted to alcohol. We used 1030 control individuals with self-reported height and weight. A total of 12 single nucleotide polymorphisms (SNP) within the CYP2A6 gene were available. Obesity was determined as a BMI ≥30: 30–34.9 (Class I obesity) and ≥35 (Class II and III obesity). Animal experiment study: CYP2A5 knockout ( cyp2a5 −/− ) mice and wild type ( cyp2a5 +/+ ) mice were fed HFD for 14 weeks. Body weight was measured weekly. After an overnight fast, the mice were sacrificed. Liver and blood were collected for biochemical assays. Results Single marker analysis showed that three SNPs (rs8192729, rs7256108, and rs7255443) were associated with class I obesity ( p < 0.05). The most significant SNP for obesity was rs8192729 (odds ratio (OR) = 1.94, 95% confidence intervals = 1.21–3.10, p = 0.00582). After HFD feeding, body weight was increased in cyp2a5 −/− mice to a greater extent than in cyp2a5 +/+ mice, and fatty liver was more pronounced in cyp2a5 −/− mice than in cyp2a5 +/+ mice. PPARα deficiency in cyp2a5 −/− mice developed more severe fatty liver, but body weight was not increased significantly. Conclusion CYP2A6 is associated with human obesity; CYP2A5 protects against obesity and NAFLD in mice. PPARα contributes to the CYP2A5 protective effects on fatty liver but it opposes to the protective effects on obesity.